Setting Fire to the Present: On Old Age in the Late Poetry of Haim Gouri and Ori Bernstein - Herzog, Omri; Shenker, Yael (MiKAN, 2024)
This article proposes a reading of the late work of two Israeli poets, Haim Gouri and Ori Bernstein, which deals with aging and is written from an old body. We explore the poetic modes on which these poets draw to express physical weakening, memories of the past, and the nearness of death. To this end, we use two interpretative perspectives regarding late style, by Edward Said and Haim Hazan. We look at how these poets’ late style is shaped by the poetic generation from which they sprang, and which they observe from the distance of years. Despite major differences between them, Haim Gouri and Ori Bernstein both write old age in a way aimed to extricate themselves from their early writing, impelled either by a desire for rehabilitation, or a consciousness of brokenness and betrayal. Haim Gouri seeks to free himself from the objects of his early poetry as well as his status as the representative voice, the one who spoke in the name of many, or the living poet who speaks in the name of the dead. His later work struggles to shake off that voice, yet simultaneously judges it by the vital, rushed, even cruel perspective of a contemporary consciousness. Bernstein’s poetry responds ironically to the individualism of his generation. The focus on the speaking self moves from carrying a poetic message into constituting a heavy melancholic burden, as the body of the poetic subject declines. Both poets aspire to cast off words that failed, while engaging, instead, with the present of aging - each in their own way: Gouri wants to truly live, to continue writing just a little more; Bernstein wants to truly die, detach himself from treacherous poetry, and devote himself to nothingness. Through their late style, they help to turn our gaze at the meaning of old age in contemporary Israeli poetry.